A 9.38-bit, 422nW, high linear SAR-ADC for wireless implantable system - Silpa Kesav Velagaleti; Nayanathara K. S.; Madhavi B. K. (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
In wireless implantable systems (WIS) low power consumption and linearity are the most prominent performance metrics in data acquisition systems. successive approximation register-analog to digital converter (SAR-ADC) is used for data processing in WIS. In this research work, a 10-bit low power high linear SAR-ADC has been designed for WIS. The proposed SAR-ADC architecture is designed using the sample and hold (S/H) circuit consisting of a bootstrap circuit with a dummy switch. This SAR-ADC has a dynamic latch comparator, a split capacitance digital to analog converter (SC-DAC) with mismatch calibration, and a SAR using D-flipflop. This architecture is designed in 45 nm CMOS technology. This ADC reduces non-linearity errors and improve the output voltage swing due to the usage of a clock booster and dummy switch in the sample and hold. The calculated outcomes of the proposed SAR ADC display that with on-chip calibration an ENOB of 9.38 (bits), spurious free distortion ratio (SFDR) of 58.621 dB, and ± 0.2 LSB DNL and ± 0.4LSB INL after calibration.